SYSTEMATIC LITERATURE REVIEW: KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK DITINJAU DARI BERBAGAI ASPEK - Nursupiamin Nursupiamin; Rafiq Badjeber (Koordinat Jurnal MIPA, 2022)
Mathematical problem-solving ability is one of the standard processes in learning mathematics, but mathematical communication skills in Indonesia are still low. The biggest cause is the difficulties experienced by students in solving problem-solving problems and when translating everyday life problems into mathematical models. This research was structured referring to the purpose of conducting a literature review regarding aspects that are considered to correlate in determining students' mathematical communication skills. The research method used is the Systematic Literature Review which collects data by documenting and reviewing all relevant research articles related to communication skills in terms of various aspects, especially related to story questions published in the 2015-2021 period. The articles used in this study were 11 journals obtained from the Google Scholar database. Based on this study, it was found that mathematical communication skills have a good correlation in terms of gender, personality type, cognitive style, IQ, dominant brain, learning style, conceptual ability, and the suitability of the learning model used